Granulomatous lung disease and immune reconstitution inflammatory syndrome in Whipple's disease. Issue 6 (18th June 2021) - Hofmann, Patrick; Durisch, Nina; Buetikofer, Claudia; Helmchen, Birgit Maria
Abstract : We present the case of a 70-year-old woman with a history of seronegative arthritis, recurrent pleural effusion and weight loss. A prior lung biopsy had revealed non-caseating epithelioid cell granulomas without evidence for microbial organisms on special stains. Intestinal biopsy findings where suspicious for Whipple's disease, which was confirmed by PCR testing, both on the intestinal and retrospectively on the lung tissue. Treatment with ceftriaxone resulted in clinical deterioration with fever, arthritis and recurrent pleuritis consistent with immune reconstitution inflammatory syndrome. Dose increase of glucocorticoids and therapy rotation to doxycycline and hydroxychloroquine resulted in rapid clinical improvement.